Rusijos ir Gruzijos 2008 metų karinio konflikto pateikimas Lietuvos ir Italijos periodinėje spaudoje informacinio karo aspektu - Martišius, Mantas; Navickaitė, Vilija (Information & Media, 2009)
Straipsnyje informacinio karo aspektu nagrinėjamas 2008 metų rugpjūtį kilusio penkių dienų konflikto tarp Rusijos ir Gruzijos atspindėjimas Lietuvos ir Italijos internetinėje žiniasklaidoje. Nagrinėjamas informacinio karo vaidmuo 2008 metų Rusijos ir Gruzijos kare. Aptariamas karinio konflikto pateikimas pasirinktose žiniasklaidos priemonėse tiriamuoju laikotarpiu. Nagrinėjama, kaip buvo pristatoma didėjanti įtampą Šiaurės Kaukazo regione. Gvildenama, kokią poziciją kariaujančių šalių atžvilgiu užėmė Lietuvos ir Italijos tyrimui pasirinktos žiniasklaidos priemonės. Nagrinėjama informaciniame kare pasireiškianti tendencija, kai žiniasklaida ima palaikyti savo valdžios oficialiąją poziciją kariaujančių šalių atžvilgiu. Presenting the 2008 Russia–Georgia war in Lithuanian and Italian press in information warfare aspect Mantas Martišius, Vilija Navickaitė Summary The five-day war between Russia and Georgia in the summer of 2008 during the Olympic games in Beijing immediately concentrated the world’s mass media attention and raised public discussions on the reasons and consequences of this confrontation. The paper claims to verify the hypothesis that the Italian mass media were favourable to Russia’s position considering the official Italian–Russian close relationships and the personal friendship of recent Italian prime minister and media magnate Silvio Berlusconi with Russia’s expresident and recent prime minister Vladimir Putin. On the other hand, Lithuanian mass media should have been a favourable to Georgia’s position considering the common historical experience and the official Lithuania’s governmental support of this country advocated in the European Union and NATO membership procedure. By holding the empirical analysis of the mass media publications, the objectives of the research were the following: 1) to explore the concept of information warfare; 2) to determine the contribution of the media to the conflict coverage; 3) to analyze the Italian and Lithuanian mass media publications by selected criteria: a) to analyze the publications of Lithuanian mass media by quantitative and qualitative methods; b) to analyze the publications of Italian mass media by quantitative and qualitative methods; 4) to analyze the reasons for such attitude. According to the empirical research, the evidence of information warfare is clear. Lithuanian mass media into the information warfare. It surrendered to the rule engaged during the war to support the government. This shows that Lithuanian mass media deviated from the truth and objectivity. During the war, Lithuanian society received biased partial information. News from the five-day war between Russia and Georgia were unreliable and incomplete. Ther were no neutral and balanced answers to the questions why the war broke out, who started the fire, how it developed. This happened not just because Russia and Georgia waged the information war, but also as a responsibility of Lithuanian mass media to follow the politics of support to Georgia. The Italian mass media took a neutral position, the type of analyzed mass media which belongs to central left political parties recently placing in opposition and criticizing the S. Berlusconi decision to be favourable to Russia’ s position. Therefore, the conflict between Russia and Georgia was “their” and the Italian mass media just informed society about the events. Thus, the hypothesis was corroborated only in part.